OPTIMASI PROSES PEMBUATAN METIL ESTER SULFONAT (MES) DARI MINYAK JARAK PAGAR (Jatropha Curcas L.) DAN PENGARUHNYA TERHADAP NILAI TEGANGAN ANTARMUKA MENGGUNAKAN METODE PERMUKAAN RESPON - Hidayati, Sri; Zuidar, A. Sapta; Yanto, Ferdi (Jurnal Teknologi & Industri Hasil Pertanian, 2009)
The objectives of this research were to obtain the optimum condition for processing of MES from methyl ester of jatropha oil, and to characterize MES processed at its  optimum condition.  The experiment was designed in a factorial 24 with four free variables: temperatures of sulfphonation (X1) consisted of : 60oC, 80oC, 100oC, 120oC, and 140oC;  the length  of sulfonation (X2) consisted of :  1,5 hours, 3 hours, 4,5 hours, 6 hours, and 7,5 hours;  methanol concentrations (X3) consisted of :  10%, 20%, 30%, 40%, and 50%;  purification temperatures (X4) consist of :  30oC, 40oC, 50oC, 60oC, and 70oC.  Data were analysed using response surface methodology of Minitab 14 software. The results showed that combination condition of the optimum treatment for interfacial tension was achieved when the process was carried out at temperature of sulphonation (X1) 102oC, time of sulphonation (X2) 3,9 hour, methanol concentration (X3) 38%, and temperature of purification (X4) 50oC with the IFT value stationer point at 3,418457 dyne/cm.  MES from methyl ester of jatropha oil processed at the optimum condition has the characteristics of  absorbance value  of 0,3 and emulsion stability  of 45%. Key words:  surfactant, methyl ester sulphonate, interfacial tension.